2019
DOI: 10.1016/j.anr.2019.08.001
|View full text |Cite
|
Sign up to set email alerts
|

The Process of Structuring Community Health Needs by Public Health Nurses Through Daily Practice: A Modified Grounded Theory Study

Abstract: It is extremely difficult to apply the model learned in basic education for public health nurses (PHNs) to conduct community health assessments. The purpose of this study was to clarify the process by which community health needs can be structured through PHNs' daily practice. Methods: Semistructured interviews were conducted in 29 PHNs, and continuous comparative analysis using a qualitative study was performed with a modified grounded theory approach. Results: The participants "used their five senses to unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The low percentage of model utilizing PHNs in this study was caused by both the working environment and the lack of practical model. Okura (2019) indicated that PHNs were too overwhelmed with supporting high risk cases to develop community need based activities. She clarified the process by which municipal PHNs identified health problems in their daily practice using qualitative research.…”
Section: Discussionmentioning
confidence: 99%
“…The low percentage of model utilizing PHNs in this study was caused by both the working environment and the lack of practical model. Okura (2019) indicated that PHNs were too overwhelmed with supporting high risk cases to develop community need based activities. She clarified the process by which municipal PHNs identified health problems in their daily practice using qualitative research.…”
Section: Discussionmentioning
confidence: 99%
“…The results of several qualitative studies highlight that community health nursing plays a major role in addressing health disparities that occur in society. This needs to be supported by the presence of nurses' self-ability in carrying out nursing care, namely by building confidence and skills (Aston et al, 2009), able to reflect on and learn from experience (M. A Mabhala, 2013), have a keen interest in performing tasks, and are able to provide supervision to the community (Okura, 2019).…”
Section: Self-nurse Abilitymentioning
confidence: 99%
“…Community health nursing has grown very significantly in recent years. This development must also go hand in hand with improving the quality of nursing care by providing innovation, active involvement, and a skilled ability to provide quality services (Markham & Carney, 2008), conduct and evaluate clinical practice (Okura, 2019). This is used as the basis for a health strategy to obtain the health status of an individual or population related to quality of life (Mabhala, 2013).…”
Section: Quality Nursing Carementioning
confidence: 99%
See 2 more Smart Citations